2021
DOI: 10.31234/osf.io/dnvrj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Filling the gaps: Cognitive control as a critical lens for understanding mechanisms of value-based decision-making

Abstract: Research into value-based decision making has made tremendous progress in identifying behavioral and neural correlates of choice value. However, these correlates have been primarily viewed through a field-specific lens, focusing on how they contribute to the evaluation and selection between options to arrive at a choice. Here, we reveal blind-spots resulting from this limited perspective, and how they can be filled in through taking the perspective of cognitive control. We highlight three particular insights t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 220 publications
(266 reference statements)
0
3
0
Order By: Relevance
“…Signatures of this evidence accumulation process have been identified throughout the brain [131,132], with some notable differentiation between neural circuits that appear to track the accumulation of information about which options are the most valuable (e.g., in orbital and/or ventromedial PFC [128,133,134]); which response is the best overall (e.g., in dorsomedial prefrontal or lateral intraparietal regions [131,135,136]); and what motor action to implement (e.g., in premotor and/or motor cortices [137][138][139]). However, as we discuss next, the interpretation of these signals as indexing evidence accumulation per se, rather than a covariate thereof, is a matter of significant debate [140].…”
Section: Transforming Values Into Choicementioning
confidence: 99%
See 2 more Smart Citations
“…Signatures of this evidence accumulation process have been identified throughout the brain [131,132], with some notable differentiation between neural circuits that appear to track the accumulation of information about which options are the most valuable (e.g., in orbital and/or ventromedial PFC [128,133,134]); which response is the best overall (e.g., in dorsomedial prefrontal or lateral intraparietal regions [131,135,136]); and what motor action to implement (e.g., in premotor and/or motor cortices [137][138][139]). However, as we discuss next, the interpretation of these signals as indexing evidence accumulation per se, rather than a covariate thereof, is a matter of significant debate [140].…”
Section: Transforming Values Into Choicementioning
confidence: 99%
“…Work has shown that a person can evaluate these same metacognitive signals of confidence/uncertainty while making their choice (e.g., based on the overall strength of evidence), and can make online adjustments to their choice strategy accordingly (e.g., increasing their decision threshold when less confident) [143,145,149,150]. Metacognitive evaluations thus offer a prominent alternative explanation for putative neural correlates of evidence accumulation, including estimates of the decision variable itself [127,140,[151][152][153][154].…”
Section: Transforming Values Into Choicementioning
confidence: 99%
See 1 more Smart Citation